2014
DOI: 10.2141/jpsa.0130022
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Cassava Pulp Feedstuff Fermented with <i>A. oryzae</i>, on Growth Performance, Nutrient Digestibility and Carcass Quality of Broilers

Abstract: Cassava pulp contains a lot of starch, but low amounts of protein and high fiber content which limits its use as a feedstuff for broilers. However, fermentation of this pulp with Aspergillus oryzae (A. oryzae) to improve its protein content may increase its usefulness in broiler diets. Therefore, two experiments were conducted to evaluate the potential use of fermented cassava pulp (FCP) in broilers. In experiment 1 the effects of FCP on nutrient digestibility and retention were studied. FCP was prepared using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 23 publications
(24 reference statements)
6
50
2
1
Order By: Relevance
“…In terms of the antioxidant property of the fungus, it might have a minimal effect on the liver weight, as Jang et al (2014) reported no effect of antioxidants (vitamins C and E) on the relative weight of liver in broiler chicks. Eventually, the lower liver weight in the present study may confirm that the toxicological effect of urea used as a nitrogen source in the fermentation process did not appear in broiler chicks (Khempaka et al, 2014;Sugiharto et al, 2016a). Birds in AC-FCP group had greater weight of spleen than birds in other experimental groups.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In terms of the antioxidant property of the fungus, it might have a minimal effect on the liver weight, as Jang et al (2014) reported no effect of antioxidants (vitamins C and E) on the relative weight of liver in broiler chicks. Eventually, the lower liver weight in the present study may confirm that the toxicological effect of urea used as a nitrogen source in the fermentation process did not appear in broiler chicks (Khempaka et al, 2014;Sugiharto et al, 2016a). Birds in AC-FCP group had greater weight of spleen than birds in other experimental groups.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, diets containing AC-FCP tended to reduce the feed cost per kilogram live weight gain of broiler chicks. In an earlier work, Khempaka et al (2014) reported that inclusion of Aspergillus oryzae-fermented cassava pulp up to 16% of diets did not significantly affect the digestibilities of DM and organic matter or nitrogen retention in broiler chicks. Accordingly, the present data showed no significant effect of dietary AC-FCP and/or AGPs inclusion on the digestibilities of DM and organic matter and nitrogen retention in broiler chicks.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Fermentation with A. niger was shown to increase the hemicellulose and amylopectin contents and metabolizable energy value of unpeeled cassava root meal for birds [68], suggesting that fermenting fungal organisms are able to release digestive enzymes which pre-digest the substrate, hence increasing the availability of nutrients [69]. Higher crude protein content and increased starch digestibility were recorded by [70] after fermenting cassava pulp with Aspergillus oryzae.…”
Section: Microbial Processing Of Cassava For Poultry Feedingmentioning
confidence: 99%
“…Therefore, it needs a feed processing technology, such as fermentation, to reduce the fiber content and increase the nutrient digestibility. Yeast is a natural ingredient that is widely used as an inoculum in fermentation processes of poultry feedstuff (Khempaka et al, 2014;Sandi et al, 2016;Yosi et al, 2016). In addition, the yeast is also used as a feed supplement in poultry rations that can stimulate the growth process (Yalçın et al, 2013).…”
Section: Introductionmentioning
confidence: 99%